2021
DOI: 10.3390/molecules26195981
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous Stereochemical Assignment of Cyclo(Phe-Pro), Cyclo(Leu-Pro), and Cyclo(Val-Pro) by Electronic Circular Dichroic Spectroscopy

Abstract: 2,5-diketopiperazines (DKPs) are cyclic dipeptides ubiquitously found in nature. In particular, cyclo(Phe-Pro), cyclo(Leu-Pro), and cyclo(Val-Pro) are frequently detected in many microbial cultures. Each of these DKPs has four possible stereoisomers due to the presence of two chirality centers. However, absolute configurations of natural DKPs are often ambiguous due to the lack of a simple, sensitive, and reproducible method for stereochemical assignment. This is an important problem because stereochemistry is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…There have been multiple reports where the diketopiperazine cyclo-( L -Phe -L -Pro) was found to modulate/interfere with the cell signaling of quorum sensing systems [ 39 , 40 , 41 ]. The ECD of compound 5 is comparable to that of a L , L configuration as reported by Domzalski et al [ 31 ]. In another report, cyclo-( L -Phe -L -Pro) inhibited the Ptst promoter of agr quorum sensing system of S. aureus biofilms [ 42 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…There have been multiple reports where the diketopiperazine cyclo-( L -Phe -L -Pro) was found to modulate/interfere with the cell signaling of quorum sensing systems [ 39 , 40 , 41 ]. The ECD of compound 5 is comparable to that of a L , L configuration as reported by Domzalski et al [ 31 ]. In another report, cyclo-( L -Phe -L -Pro) inhibited the Ptst promoter of agr quorum sensing system of S. aureus biofilms [ 42 ].…”
Section: Resultssupporting
confidence: 84%
“…The structures of the cyclic dipeptides were elucidated by 1D and 2D NMR as well as corroborated with the literature (Table S1 and Figure S2A) [26][27][28][29][30]. Comparison of the CD spectra of compounds 2 to 5 (Figure S2B) to those found in the literature followed the 2S,2 ′ S (3S,6S for 2 to 4 and 3S,8aS for 5 in their IUPAC nomenclature) [31][32][33][34].…”
Section: Mzminesupporting
confidence: 84%
“…In addition, cyclo(Val-Pro) is a cyclic dipeptide belonging to 2,5-diketopiperazines (DKPs), and the chemical structure of these cyclic dipeptides is relatively stable and not easily digested into amino acids. 73 It has been reported that Nmethyl derivatives of DKPs easily cross the blood−brain barrier (BBB) and can be used as BBB-shuttles, which could facilitate the transport of therapeutic substances across the BBB. 74 The composition of HCE is very complex, and its bioactive components have not yet been fully discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies using old mice, 18–24 months of age, could provide more evidence for the application of cyclo­(Val-Pro) in the aged population. In addition, cyclo­(Val-Pro) is a cyclic dipeptide belonging to 2,5-diketopiperazines (DKPs), and the chemical structure of these cyclic dipeptides is relatively stable and not easily digested into amino acids . It has been reported that N -methyl derivatives of DKPs easily cross the blood–brain barrier (BBB) and can be used as BBB-shuttles, which could facilitate the transport of therapeutic substances across the BBB .…”
Section: Discussionmentioning
confidence: 99%